The Critical Bricolage: Uniquely Advancing Organizational and Nursing Knowledge on the Subject of Rapid and Continuous Change in Health Care. Issue 4 (23rd October 2015) - McMillan, Kim
Change in health care has become rapid and continuous. Much decision-making processes guiding change management are derived from organizational literature which is heavily reflective of managerial perspectives. These perspectives represent and aim to serve only a small subgroup of organizational members. However, change is complex, fragile, and has higher rates of success and sustainability when change management strategies reflect a multitude of organizational voices. There is a dearth of literature exploring the intersect between organizational and nursing discourses on the subject of rapid and continuous change in health care. Multitheoretical, multimethodological, and multidisciplinary informed approaches to methodological decision making are needed to link organizational and nursing discourses in ways that will offer alternative perspectives on the subject of change. Furthermore, critically guided multitheoretical, multimethodological, and multidisciplinary methodologies are timely and important in organizational research. Critically guided research seeks to analyze taken-for-granted assumptions and institutionalized practices seeking alternative perspectives and alternative sources of organizational knowledge. Exploring alternative perspectives from a critical lens recognizes the impact predominant discursive influences have on change management and the subsequent impact on organizational members' working lives. This article will explore how Kincheloe's discussions of the critical bricolage serve to support combining critical organizational methodologies (guided by Alvesson and Deetz) with a voice-centered relational method of data analysis (guided by Brown and Gilligan) to create a critical interpretive methodology that explores the voices of nurses as they experience rapid and continuous change in health care.